Overexpression of the Glutathione Peroxidase 5 (RcGPX5) Gene From Rhodiola crenulata Increases Drought Tolerance in Salvia miltiorrhiza - Zhang, Lipeng; Wu, Mei; Teng, Yanjiao; Jia, Shuhang; Yu, Deshui; Wei, Tao; Chen, Chengbin; Song, Wenqin (Frontiers in Plant Science, 2019)
Excessive cellular accumulation of reactive oxygen species (ROS) due to environmental stresses can critically disrupt plant development and negatively affect productivity. Plant glutathione peroxidases (GPXs) play an important role in ROS scavenging by catalyzing the reduction of H2O2 and other organic hydroperoxides to protect plant cells from oxidative stress damage. RcGPX5, a member of the GPX gene family was isolated from a traditional medicinal plant Rhodiola crenulata and constitutively expressed in Salvia miltiorrhiza under control of the CaMV 35S promoter. Transgenic plants showed increased tolerance to oxidative stress caused by application of H2O2 and drought, and had reduced production of malondialdehyde (MDA) compared with the wild type. Under drought stress, seedlings of the transgenic lines wilted later than wild type and recovered growth one day after re-watering. In addition, the reduced glutathione (GSH) and total glutathione (T-GSH) contents were higher in the transgenic lines, with increased enzyme activities including glutathione reductase (GR), ascorbate peroxidase (APX), and GPX. These changes prevent H2O2 and O2- accumulation in cells of the transgenic lines compared with wild type. Overexpression RcGPX5 alters the relative expression levels of multiple endogenous genes in Salvia miltiorrhiza, including transcription factor genes and genes in the ROS and ABA pathways. In particular, RcGPX5 expression increases the mass of Saliva miltiorrhiza roots while reducing the concentration of the active ingredients. These results show that heterologous expression of RcGPX5 in Saliva miltiorrhiza can affect the regulation of multiple biochemical pathways to confer tolerance to drought stress, and RcGPX5 might act as a competitor with secondary metabolites in the Saliva miltiorrhiza response to environmental stimuli.